Bioregional Border Governance: State, Indigenous Peoples, and Ecological Connectivity in the Indonesia–Papua New Guinea Borderland - Melyana Ratana Pugu (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: … Objective: This research aims to analyze the dynamics of border governance between Indonesia and Papua New Guinea from a multidimensional perspective, examine the role and involvement of indigenous peoples, and evaluate the importance of a bioregional approach in maintaining flora and fauna connectivity in the Pacific region. Furthermore, this research aims to formulate an integrated border governance model capable of combining the interests of state sovereignty, local community welfare, and the sustainability of transboundary ecosystems. Methods: This research uses a qualitative-descriptive approach with a descriptive-analytical design. The data used is entirely secondary data obtained through library research and internet-based research from indexed scientific journals, policy documents, and relevant institutional reports. To ensure data validity, this research applies triangulation techniques by comparing various data sources from policy, academic, and empirical perspectives. Results: The results show that border governance between Indonesia and Papua New Guinea is still dominated by a security-based approach and has not fully integrated social and ecological dimensions. Indigenous peoples have a strategic role in maintaining social stability and environmental sustainability through local knowledge and traditional practices, yet their involvement in formal policy remains limited. Additionally, the bioregional connectivity of flora and fauna in the Melanesian region faces serious threats due to habitat fragmentation, natural resource exploitation, and climate change, which cannot be effectively addressed through administrative boundary-based approaches alone. As a key output, this research produces a conceptual model of integrated border governance based on collaboration between the state and indigenous peoples using a bioregional approach. This model emphasizes the integration of multilevel governance between central government, local government, and indigenous peoples, and prioritizes area management based on transboundary ecosystem units. This model is expected to serve as a reference for formulating more inclusive, adaptive, and sustainable border policies. Conclusion: This research also identifies a research gap in the literature, namely the limited number of studies that comprehensively integrate border governance, the role of indigenous peoples, and bioregional approaches within a single analytical framework. Therefore, future research is advised to develop primary data-based studies through field approaches, empirically test the proposed model, and expand the study to other border areas in the Pacific region to strengthen the generalizability of the findings.